The role of the e3 ligase cbl-B in murine dendritic cells. - Stephanie Wallner (Public Library of Science (PLoS), 2013)
Dendritic cells (DCs) are potent antigen-presenting cells with a promising potential in cancer immunotherapy. Cbl proteins are E3 ubiquitin ligases and have been implicated in regulating the functional activity of various immune cells. As an example, c-Cbl negatively affects DC activation. We here describe that another member of the Cbl-protein family (i.e. Cbl-b) is highly expressed in murine bone-marrow-derived DCs (BMDCs). Differentiation of cblb-/- bone marrow mononuclear cells into classical BMDCs is unaltered, except enhanced induction of DEC-205 (CD205) expression. When tested in mixed-lymphocyte reaction (MLR), cblb-/- BMDCs exhibit increased allo-stimulatory capacity in vitro. BMDCs were next in vitro stimulated by various toll like receptor (TLR)-agonists (LPS, Poly(I:C), CpG) and exposed to FITC-labeled dextran. Upon TLR-stimulation, cblb-/- BMDCs produce higher levels of proinflammatory cytokines (IL-1α, IL-6 and TNF-α) and exhibit a slightly higher level of FITC-dextran uptake. To further characterize the functional significance of cblb-/- BMDCs we tested them in antigen-specific T cell responses against ovalbumin (OVA) protein and peptides, activating either CD8(+) OT-I or CD4(+) OT-II transgenic T cells. However, cblb-/- BMDCs are equally effective in inducing antigen-specific T cell responses when compared to wildtype BMDCs both in vitro and in vivo. The migratory capacity into lymph nodes during inflammation was similarly not affected by the absence of Cbl-b. In line with these observations, cblb-/- peptide-pulsed BMDCs are equally effective vaccines against OVA-expressing B16 tumors in vivo when compared to wildtype BMDCs. We conclude that in contrast to c-Cbl, Cbl-b plays only a limited role in the induction of Ag-specific T cell responses by murine BMDCs in vitro and in vivo.